Causal dynamics among foreign portfolio investment volatility, financial deepening and capital markets in low income countries - Kuziva Mamvura; Mabutho Sibanda; Rajendra Rajaram (SPOUDAI - Journal of Economics and Business, 2020)
This study investigated the directional linkages among net foreign portfolio investment volatility, financial deepening and capital market performance in low-income Southern African Development Community (SADC) countries employing a dynamic panel vector error correction model (P-VECM) on unbalanced quarterly panel data for the period spanning from 2000 to 2015. Using cointegration analysis in P-VECM, the study established the existence of a long-run equilibrium relationship among the variables. The pairwise test demonstrated that there is a unidirectional causality relation from net portfolio investment volatility to financial deepening in low income SADC markets. Furthermore, the results indicate a bidirectional causal relationship between real gross domestic product (GDP) and the performance of capital markets, suggesting that as GDP grows, capital markets perform better or vice versa. Additionally, the results reveal that real GDP unilaterally leads both net portfolio investment volatility and financial deepening in these economies. Conversely, the pairwise test distinctively indicates that capital market performance is neither causally related to financial deepening nor to the variability of foreign portfolio investment flows in the selected economies. It is therefore recommended that policy makers in low income economies should embark on programmes that attract more players in the domestic markets to encourage the deepening and performance of financial markets, which will in turn strengthen the long run causality with net foreign portfolio investment flows.
Keywords: F21; F32; E44; G15; 330; Foreign portfolio investment volatility; financial deepening; Granger causality; capital market performance; P-VECM